Vertical school: innovative urban school design strategies in Kuala Lumpur, Malaysia - Mokhtar, Khairyl Fahmy; Denan, Zuraini; Asif, Nayeem (University of Technology Sarawak, 2024)
Rapid urbanization in Kuala Lumpur has led to increased demand for schools, resulting in a scarcity of land for traditional horizontal school designs. The lack of space poses challenges in fostering effective learning environments and addressing the psychological needs of students. This study aims to propose design strategies for Vertical Schools in Kuala Lumpur to provide conducive and modern learning environments suitable for the 21st century. By examining case studies of existing vertical schools, the research seeks to develop recommendations for the next generation of school designs. Three case studies, including the School of Arts in Singapore, Singapore International School in Hong Kong, and William Jones College Preparatory School in Chicago, were selected through a sampling process to reflect regional characteristics and challenges. The comparative analysis was conducted through tabular examination, facilitating a systematic comparison of architectural elements and student activities. The study recommends several design strategies for urban vertical schools, including providing outdoor spaces, optimizing circulation, integrating facilities, utilizing natural light, designing flexible room layouts, and maximizing vertical space utilization. These recommendations aim to enhance collaboration, foster community interaction, and promote student well-being and learning experiences. While this study provides valuable insights into vertical school design, further research is needed to refine design strategies and adapt to evolving educational needs and urban contexts. Ongoing research and development in vertical school architecture are essential to address future challenges and optimize learning environments for students in urban areas.